EFEKTIVITAS PENGGUNAAN METODE EXPLICIT INSTRUCTION TERHADAP KETERAMPILAN AKUNTANSI DASAR SISWA SMK IMMANUEL II SUNGAI RAYA - Desi, Fransiska; Herkulana, Herkulana; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to determine the effectiveness of the use of explicit instruction methods for basic accounting skills of class X AK Immanuel Christian Vocational School 2 Sungai Raya. The method used is an experiment with quasi design experimental design with a Non Equivalent Control Group Design research design. In this study, the experimental class was the X AK 1 class, while the control class was X AK 2. The data collection used an instrument in the form of a standardized essay test that had been tested for validity and reliability. The results showed that there were differences in the average student learning outcomes between the experimental class and the control class. The results of the calculation data obtained the results of the average value of the experimental class students amounting to 82.21 and the average learning outcomes of the control class students at 72.38. The difference in the average post-test of both classes, namely the experimental class and the control class, obtained the value of t count of 2.75 while the t table with a significance level of 5% or 0.05 So tested two sides 0.025 with the degree of magnitude n-k or 84-2 = 82 can be seen t table of 1.989 Value t count> t table (2.756> 1.989). So it can be concluded that Ho is rejected and Ha is accepted, seen from the significant value obtained a significant value (Sig.2-tailed) that is equal to 0.007 and smaller than 0.05 then Ho is rejected and Ha is accepted which means there is effectiveness in using explicit instruction learning methods against basic accounting skills in class X AK Immanuel Christian Vocational School 2 Sungai Raya. Based on the calculation of the effect size the results obtained are 0.60 medium categories, so the effective level is classified as mediuml. Keywords: Explicit Instruction, Basic Accounting Skills, Special Journal